Reminiscences: The Arctic Institute in the 1960s - Reed, John C. (ARCTIC, 1987)
The author was the executive director of the Arctic Institute from 1961 until 1968 and his reminiscences deal with some of the financial problems and practices of the Institute during his term. Clearly, during his time in office, the provision of financial support for the organization was a dominant concern of the board and of the director. The increase in arctic interest and involvement in both Canada and the United States a little before and into the 1960s pushed the Institute toward an emphasis on service-type activities. The author was convinced of the growing importance of the Arctic to Canada and the United States. He was impressed by the stature of the members of the Board of Governors and others with whom he worked, and obviously he enjoyed directing the organization and felt that it contributed to a real and increasing need.Key words: Arctic Institute of North America, international cooperation, research funding, arctic research, Arctic Bibliography L'auteur a été directeur exécutif de l'Institut arctique de l'Amérique du Nord de 1961 à 1968, et il évoque un certain nombre de problèmes financiers et de pratiques de l'Institut au cours de son mandat. À cette époque, le Conseil et le directeur étaient de toute évidence, surtout préoccupés par la recherche d'un support financier pour cet organisme. Un intérêt accru en ce qui concernait l'Arctique, ainsi que la double implication du Canada et des États-Unis dans cette région, à fin des années 50 et dans les années 60 ont obligé l'Institut à mettre l'accent sur des activités reliées aux services.L'auteur était convaincu de l'importance croissante de l'Arctique pour le Canada et les États-Unis. Il était très impressionné par la stature des membres du Conseil des Gouverneurs et celle d'autres personnes avec qui il travaillait, et il était fier de diriger cet organisme dont l'importance se faisait de plus en plus sentir.Mots clés: Institut arctique de l'Amérique du Nord, coopération internationale, subventions de recherche, recherche sur l'Arctique, ...